Structure of the molecular receptor 1,4,7,10-tetrakis[(S)-2-hydroxy-2-phenylethyl]-1,4,7,10-tetraazacyclododecane: A combined X-ray crystallographic and theoretical study producing an assessment of the crystal packing energy - Smith, C.; Buntine, Mark; Lincoln, S.; Taylor, M.; Wainwright, K. (CSIRO Publishing, 2006)
X-Ray crystallography demonstrates that the guest molecule binding cavity within the molecular receptor ligand 1,4,7,10-tetrakis[(S)-2-hydroxy-2-phenylethyl]-1,4,7,10-tetraazacyclododecane, (S)-thpec12, is a poorly defined conical region stabilized by three O-H center dot center dot center dot O hydrogen bonds and a single O-H center dot center dot center dot N hydrogen bond. Two similar, but crystallographically independent, molecules exist within the unit cell. Ab initio calculations, using Gaussian 03 (LanL2DZ basis set at the Hartree-Fock level of theory), predict that these have steric energies of 97.73 and 97.06 kJ mol(-1), respectively, above that of the minimum energy ( gas phase) conformer of the same hydrogen-bonding configuration, which is believed to be the structure of global minimum energy. The mean of these energies (97.4 kJ mol(-1)) represents a best estimate of the crystal packing energy for (S)-thpec12, some of which is seen to be expended in rotating the phenyl rings away from the positions favoured in the gas phase. The ability of the Cd-II complex of (S)-thpec12 to act as a molecular receptor for aromatic anions is demonstrated by the isolation of two inclusion compounds in which p-nitrophenolate and anthraquinone-2-sulfonate are retained.